Near-infrared and visible dual emissive transparent nanopaper based on Yb(III)–carbon quantum dots grafted oxidized nanofibrillated cellulose for anti-counterfeiting applications. Issue 1 (January 2018) - Zhang, Zhao; Chang, Hui; Xue, Bailiang; Zhang, Sufeng; Li, Xinping; Wong, Wai-Kwok; Li, Kecheng; Zhu, Xunjin
Abstract We report a novel near-infrared (NIR) and visible dual emissive transparent Yb3+ -nanopaper, which is produced from Yb3+ -CQDs grafted oxidized nanofibrillated cellulose (Yb3+ -CQDs-ONFC) using a press-controlled extrusion film-making method. The Yb3+ -nanopaper exhibits excellent properties, including high transparency (90%), good flexibility, visible fluorescence and NIR phosphorescence. The morphology and chemical structures of Yb3+ -nanopaper are investigated with SEM, TEM, XRD, XPS, ICP-OES and FT-IR spectroscopy. The experimental results show that the Yb3+ -CQDs have been successfully grafted onto ONFC matrix, and the Yb3+ -CQDs are well dispersed in nanopaper with strong visible-NIR dual emission under only one UV excitation. In the Yb3+ -nanopaper, CQDs not only act as visible fluorescence "emitter" but also as "antenna" sensitizing Yb3+ ions with NIR characteristic luminescence. And the sensitization of the energy transfer pathway is mainly through singlet state (1 LC). Furthermore, the surface passivation of Yb3+ -CQDs with ONFC produces an enhanced NIR luminescence by eight times in intensity. Of importance here is that high level security codes of Yb3+ -nanopaper can be achieved in three fashions including colour tuning from blue to yellow, NIR/visible spectra, and nanosecond/microsecond lifetime. In addition, aqueous solution of Yb3+ -CQDs-ONFC being colourless and transparent can be applied as water-based security ink and spread on the currency note or filter paper, and the spread patterns on the filter paper are stable under water or moist environment.